An item response theory analysis of the PTSD checklist for DSM-5: Implications for DSM-5 and ICD-11. (March 2020) - Silverstein, Madison W.; Petri, Jessica M.; Kramer, Lindsay B.; Weathers, Frank W.
Highlights: To explore the psychometric properties of the PTSD Checklist (PCL-5) we used item response theory (IRT) to examine item difficulty and discrimination parameters in trauma-exposed participants. Nightmares, flashbacks, and reckless or self-destructive behavior emerged among the most difficult items and internal avoidance emerged as the least difficult items. Surprisingly, many dysphoria symptoms emerged as highly discriminating items, and traumatic amnesia and reckless or self-destructive behavior emerged as the least discriminating items. Abstract: The PTSD Checklist (PCL) is a widely used, extensively validated questionnaire for posttraumatic stress disorder (PTSD). The PCL was revised for Diagnostic and Statistical Manual of Mental Disorders, 5th Edition ( DSM-5 ; Friedman, 2013 ), and the updated version, the PCL-5, has continued the strong psychometric performance of the original version. To further explore the PCL-5's psychometric properties, we used item response theory (IRT) to examine item difficulty and discrimination parameters in separate samples of trauma-exposed undergraduates ( N = 1213) and community members ( N = 367). Considering item difficulty, nightmares, flashbacks, and reckless or self-destructive behavior emerged among the most difficult items across samples and internal avoidance emerged as the least difficult items across samples. In terms of item discrimination, inability to experience positive emotions, detachment from others, diminished interest, and negative emotions emerged as highly discriminating items in both samples, and traumatic amnesia and reckless or self-destructive behavior emerged as the least discriminating items in both samples. These results have implications for the divergent conceptualizations of PTSD in DSM-5 versus International Classification of Diseases, 11th Edition ( ICD-11 ; WHO, 2018 ). Future research should employ IRT in a clinical population.